KORELASI KONTROL GULA DARAH SEWAKTU DENGAN FUNGSI KOGNITIF PADA PASIEN LANSIA DENGAN DIABETES MELITUS TIPE 2 DI RUMAH SAKIT MUHAMMADIYAH PALEMBANG - khairani, lilis; Permana, Adhi; Fadillah, Yudi (Syifa'Medika, 2025)
Type 2 diabetes mellitus (DM) is a chronic disease that commonly affects the elderly. Hyperglycemia can accelerate cerebral vascular damage and increase the risk of cognitive impairment. Random blood glucose (RBG) testing is frequently used to monitor glycemic control in daily clinical practice. The purpose of this study was to determine the correlation between random blood glucose levels and cognitive function in elderly patients with type 2 DM. This was an observational analytical study with a cross-sectional design. Subjects were elderly patients with type 2 DM. Random blood glucose levels were measured using an enzymatic method, while cognitive function was measured using the Mini-Cog questionnaire. Statistical analysis used the spearman/pearson corerelation test. Results: The majority of patients with BG levels ?200 mg/dL had lower cognitive impairment scores than those with BG levels <200 mg/dL. There was a significant positive correlation between random blood glucose levels and cognitive scores (r=0.445;p<0.001). So it can be concluded that high random blood sugar levels are associated with decreased cognitive function in elderly people with type 2 diabetes. GDS examintaion can be an early indicator for detecting the risk of cognitive impairment in elderly type 2 diabetes patients.